2013
DOI: 10.5194/bg-10-7207-2013
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching as a factor controlling spectral characteristics of chromophoric dissolved organic matter in open ocean

Abstract: Abstract. Chromophoric dissolved organic matter (CDOM) ubiquitously occurs in marine environments and plays a significant role in the marine biogeochemical cycles. Basin scale distributions of CDOM have recently been surveyed in the global ocean and indicate that quantity and quality of oceanic CDOM are mainly controlled by in situ production and photobleaching. However, factors controlling the spectral parameters of CDOM in the UV region, i.e., spectral slope of CDOM determined at 275-295 nm (S 275−295 ) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 60 publications
(124 reference statements)
6
50
1
Order By: Relevance
“…However, for the autochthonous treatment, it decreased conspicuously until the third day (from 0.0087 to 0.0051 m −1 ) but then increased again from day 3 to day 7 until it almost returned to its original value (from 0.0051 to 0.0084 m −1 ). The increase in slope matches an increase in a CDOM (440) and has been considered by Helms et al (2008) to be a result of transformation from high to low molecular weight CDOM and is considered to be a response to photoinduced decomposition (Moran et al, 2000;Grzybowski, 2000;Yamashita et al, 2013). The initial decrease in slope during the early part of the experiment echoes observations by Yamashita et al (2013) and Fichot and Benner (2012), who attributed this phenomena to microbial degradation of bioavailable CDOM (Nelson et al, 2004).…”
Section: Cdom Photobleachingsupporting
confidence: 62%
See 2 more Smart Citations
“…However, for the autochthonous treatment, it decreased conspicuously until the third day (from 0.0087 to 0.0051 m −1 ) but then increased again from day 3 to day 7 until it almost returned to its original value (from 0.0051 to 0.0084 m −1 ). The increase in slope matches an increase in a CDOM (440) and has been considered by Helms et al (2008) to be a result of transformation from high to low molecular weight CDOM and is considered to be a response to photoinduced decomposition (Moran et al, 2000;Grzybowski, 2000;Yamashita et al, 2013). The initial decrease in slope during the early part of the experiment echoes observations by Yamashita et al (2013) and Fichot and Benner (2012), who attributed this phenomena to microbial degradation of bioavailable CDOM (Nelson et al, 2004).…”
Section: Cdom Photobleachingsupporting
confidence: 62%
“…The structural modifications in DOM and its coloured fractions that are in part conveyed through variation in S CDOM result from interplay between the input of allochthonous DOC from the catchment, the production of autochthonous DOC from the microbial digestion of phytoplankton cells and the rate at which these materials are degraded biologically and photochemically (Zhang et al, 2009b;Yamashita and Tanoue, 2004;Vantrepotte et al, 2007;Nelson et al, 1998;Yamashita et al, 2013). Newly produced autochthonous CDOM typically has a higher S CDOM coefficient compared to humic-rich allochthonous material (Bracchini et al, 2010).…”
Section: Dynamics Of Dissolved Organic Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying assumption that CDOM properties can be inferred from DOC concentrations (Shanmugam, 2011;Hestir et al, 2015) was, however, not verified in this dataset. Other recent studies also reported the complete lack of relationship between DOC and CDOM (e.g., Nelson and Siegel, 2013) because the controlling factors for DOC and CDOM were different (Yamashita et al, 2013).…”
Section: A System Driven By Cdom and Napmentioning
confidence: 96%
“…The use of spectral slopes over narrow wavelength intervals, e.g., 275-295 nm (S or S 275−295 ) have been shown to provide information on C(DOM) source, photooxidative degradation, molecular size distribution, and microbial activity with steeper slopes for example signifying lower molecular weight material and vice-versa (Blough and Del Vecchio, 2002;Helms et al, 2008). Shorter wavelength spectral slope parameters have been found to be the best indicators of photodegradation with increases in the spectral slope S strongly correlating to apparent removal of CDOM absorption (Granskog, 2012;Fichot and Benner, 2012;Yamashita et al, 2013).…”
Section: Introductionmentioning
confidence: 99%